1982
DOI: 10.1095/biolreprod26.2.337
|View full text |Cite
|
Sign up to set email alerts
|

Differential Transport of Fertilized and Unfertilized Ova in the Rat

Abstract: A possible role of the quality of eggs in the regulation of ovum transport was investigated in pseudopregnant rats. Pseudopregnancy was induced

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1987
1987
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 6 publications
0
13
0
1
Order By: Relevance
“…Presumably, as ova entered the uterus prematurely, they were lost through the vagina. This has been reported to be the case in rats [5,27,28]. Thrombocytopenia was evident in pregnant but not in pseudopregnant or cycling females.…”
Section: Discussionmentioning
confidence: 72%
“…Presumably, as ova entered the uterus prematurely, they were lost through the vagina. This has been reported to be the case in rats [5,27,28]. Thrombocytopenia was evident in pregnant but not in pseudopregnant or cycling females.…”
Section: Discussionmentioning
confidence: 72%
“…Several studies indicated that horse embryos produced prostaglandin E 2 (PGE 2 ), which mediates an acceleration of the transit to the uterus (Weber et al 1991a,b). In rats and hamsters, fertilized eggs reach the uterus at higher rates compared with the unfertilized eggs (Villalon et al 1982, Ortiz et al 1986). These findings illustrate that embryo transport is an interactive process between the embryos and the oviduct.…”
Section: Embryo Transportmentioning
confidence: 99%
“…COH is one of the common hormonal regimens used to induce ovulation, either alone or as part of the IVF/ICSI procedures (Farhi & Orvieto 2010, Berker et al 2011. Studies using in vitro maturated (IVM) human oocytes (retrieved from gonadotropin-stimulated patients) demonstrate that the wildly used oocyte morphological maturation protocol may not necessarily indicate an adequate maturation of gene expression (Jones et al 2008, Virant-Klun et al 2013. These genes are involved in meiosis (SYCP2, SGOL2 and MSH2) and are upregulated in the IVM oocytes compared with in vivo maturated oocytes.…”
Section: Epigeneticsmentioning
confidence: 99%
“…No differences have been found in rabbits (Hodgson and Pauerstein, 1976), whereas in hamsters, a marked difference in the oviductal transport of embryos and unfertilized ova has been noted (Ortiz et al, 1986). In rats, in turn, a different transport of both types of ova has been clearly observed in the uterus, but not in the oviduct (Villaldn et al, 1982). This suggested that in rats only the uterus is able to recognize differences between fertilized and unfertilized ova, or that the differences appear only at more advanced stages of preimplantation development.…”
Section: Introductionmentioning
confidence: 99%